Identifying neuropeptide Y (NPY) as the main stress-related substrate of dipeptidyl peptidase 4 (DPP4) in blood circulation - Wagner, Leona; Kaestner, Florian; Wolf, Raik; Stiller, Harald; Heiser, Ulrich; Manhart, Susanne; Hoffmann, Torsten; Rahfeld, Jens-Ulrich; Demuth, Hans-Ulrich; Rothermundt, Matthias; von Hörsten, Stephan (Neuropeptides, 2016)
Dipeptidyl peptidase 4 (DPP4; EC 3.4.14.5; CD26) is a membrane-bound or shedded serine protease that hydrolyzes dipeptides from the N-terminus of peptides with either proline or alanine at the penultimate position. Substrates of DPP4 include several stress-related neuropeptides implicated in anxiety, depression and schizophrenia. A decline of DPP4-like activity has been reported in sera from depressed patient, but not fully characterized regarding DPP4-like enzymes, therapeutic interventions and protein.Sera from 16 melancholic- and 16 non-melancholic-depressed patients were evaluated for DPP4-like activities and the concentration of soluble DPP4 protein before and after treatment by anti-depressive therapies. Post-translational modification of DPP4-isoforms and degradation of NPY, Peptide YY (PYY), Galanin-like peptide (GALP), Orexin B (OrxB), OrxA, pituitary adenylate cyclase-activating polypeptide (PACAP) and substance P (SP) were studied in serum and in ex vivo human blood. N-terminal truncation of biotinylated NPY by endothelial membrane-bound DPP4 versus soluble DPP4 was determined in rat brain perfusates and spiked sera.Lower DPP4 activities in depressed patients were reversed by anti-depressive treatment. In sera, DPP4 contributed to more than 90% of the overall DPP4-like activity and correlated with its protein concentration. NPY displayed equal degradation in serum and blood, and was equally truncated by serum and endothelial DPP4. In addition, GALP and rat OrxB were identified as novel substrates of DPP4.NPY is the best DPP4-substrate in blood, being truncated by soluble and membrane DPP4, respectively. The decline of soluble DPP4 in acute depression could be reversed upon anti-depressive treatment. Peptidases from three functional compartments regulate the bioactivity of NPY in blood.
EVALuna2:24977